Ensuring Biosphere Balance in the Context of Agricultural Waste Management - Андрейченко, Андрій Вадимович; Андрейченко, А. В.; Андрейченко, Андрей Вадимович; Andreichenko, Andrii V.; Андрейченко, Світлана Сергіївна; Андрейченко, С. С.; Андрейченко, Светлана Сергеевна; Andreichenko, Svitlana S.; Сментина, Наталія Валентинівна; Сментина, Н. В.; Сментына, Наталия Валентиновна; Smentyna, Nataliia V. (ISPC, 2021)
The article focuses on the relationship between the state of the biosphere and the development of non-waste agricultural production. The objective character of the increasing level of the agricultural business activity’s intensity, which generates considerable waste, intensifies adequate resource use. The accelerated development of the non-waste production at the agriculture becomes relevant for the rational combination of this business’s effectiveness, ecological safety and social orientation of the business and economic activities. The study specifies the role of science for setting up the “science — technology — non-waste agriculture — society” system. The article considers the importance of nonwaste agricultural production for the rational use of raw-materials and energy at the “raw materials — production — consumption — secondary raw materials” cycle and the ecological balance in the biosphere, thereby taking us closer to noosphere. The features of the “mental” attitude to the agroresidues’ problem at the national and global levels are disclosed. The article highlights the complex economic, social, ecological, and institutional indicators necessary for the effectiveness of agricultural non-waste production.

У статті йдеться про взаємозв’язок стану біосфери та розвитку безвідходного сільськогосподарського виробництва. Об’єктивний характер підвищення рівня інтенсивності сільськогосподарської діяльності, що утворює значні відходи, інтенсифікує адекватне використання ресурсів. Прискорений розвиток безвідходного виробництва в сільському господарстві стає актуальним для раціонального поєднання ефективності цього бізнесу, екологічної безпеки та соціальної спрямованості підприємницької та господарської діяльності. У дослідженні визначено роль науки у створенні системи «наука — техніка — безвідходне сільське господарство — суспільство». У статті розглянуто важливість безвідходного сільськогосподарського виробництва для раціонального використання сировини та енергії за циклом «сировина — виробництво — споживання — вторинна сировина» та екологічного балансу в біосфері, наближаючи нас до ноосфери. Розкрито особливості «ментального» ставлення до проблеми агрозалишків на національному та світовому рівнях. У статті висвітлено комплексні економічні, соціальні, екологічні та інституційні показники, необхідні для ефективності сільськогосподарського безвідходного виробництва.
Andreichenko A. Ensuring Biosphere Balance in the Context of Agricultural Waste Management / A. Andreichenko, S. Andreichenko, N. Smentyna // Philosophy and Cosmology. – Vol. 26. - ISPC, 2021. – P. 46-61.
Keywords: biosphere; resource efficiency; agro-residues; agricultural production; noosphere; circular economy; біосфера; ефективність використання ресурсів; агровідходи; сільськогосподарське виробництво; ноосфера; циркулярна економіка; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Area economics::Agricultural economics